An ecological remediation model combining optimal substrate amelioration and native hyperaccumulator colonization in non-ferrous metal tailings pond. (15th November 2022) - Song, Le; Qian, Jiazhong; Zhang, Fawang; Kong, Xiangke; Li, Hui; Luan, Song; Zhang, Qinjun; Kang, Zhiqiang; Han, Zhantao; Zhang, Zhaoji
Abstract: The vegetation deterioration and pollution expansion from non-ferrous metal tailings pond have been found in many countries leading to water soil erosion and human health risk. Conventional ecological remediation technologies of mine tailings such as capping were costly and elusive. This study provided an economic and effective model as an alternative by substrate amelioration and vegetation restoration. A field experiment was carried out on a silver tailings pond in southwest China. Tailings substrate was ameliorated by adding organic matter (decomposed chicken manure, DCM), structural conditioner (polyacrylamide, PAM), water-retaining agent (acrylic acid-bentonite water-retaining agent, AAB), and heavy metal immobilizer (biofuel ash, BFA), which were optimized by laboratory experiment. Native heavy metal hyperaccumulator, Bidens pilosa, was colonized. Vegetation coverage and plant height of Bidens pilosa reached about 80% and over 30 cm respectively after 3 months, and the turbidity of tailings leaching solution decreased by 60%. The practice showed that the proportion of available heavy metals in tailings substrate was significantly lower than that in the soil surrounding mining area. Immobilization didn't have stabilization effect on Cd, Zn, and Pb, and As was only 0.002%, phytoremediation had stabilization effect of Cd, Zn, As, and Pb were 2.5–3.5%, 1–2%, 0.25–0.5%, and 0.25–0.75%. Phytoremediation was more effective significantly in controlling heavy metal pollution risk of tailings than immobilization. These results provided a new ecological remediation OSA-NHC model, meaning a combination of optimal substrate amelioration and native hyperaccumulator colonization, which could achieve vegetation restoration and augment heavy metal pollution control in non-ferrous metal tailings pond. Graphical abstract: Image 1 Highlights: Metal tailings pond ecological remediation faces two problems: vegetation restoration and pollution control. Optimal multiple components substrate amelioration and native hyperaccumulator colonization are integrated. Proportion of available heavy metals in tailings is significantly lower than that in soil surrounding mining area. Phytoremediation is significantly better than immobilization in heavy metal control. An ecological remediation model for non-ferrous metal tailings pond is presented.